Technological diffusion as a process of societal embedding: Lessons from historical automobile transitions for future electric mobility. (June 2019) - Kanger, Laur; Geels, Frank W.; Sovacool, Benjamin; Schot, Johan
Highlights: Technological diffusion can be understood as a broader process of societal embedding. User contexts, cultural meanings, policies, and infrastructures can accelerate and stabilize new technologies. We explore case studies of automobile diffusion in the United States and the Netherlands. Applied to electric vehicles, societal embedding demands a more robust treatment of policy and agency. Abstract: Technological diffusion can be understood as a broader process of co-construction of technology and its environment. This article conceptualizes this co-construction as a process of societal embedding, in which new technologies find their place in wider societal domains, which include immediate user contexts, cultural meanings, policies, and infrastructures. This perspective helps address three under-developed dimensions in adoption models: (1) diffusion includes more actors than users/adopters, (2) user characteristics and environments are not known in advance, but are articulated during the technological diffusion process, and (3) societal embedding is full of choices and struggles that affect the directionality and thus shape of socio-technical systems. Societal embedding therefore calls importance to the "demand side" of sustainability transitions. Because electric vehicles have, so far, only achieved limited diffusion globally, we cannot use it to test and illustrate our framework. We therefore use a historical comparative research design, which utilizes the societal embedding framework with two case studies of automobile diffusion in the United States and the Netherlands between the 1880s and 1970s. We subsequently apply the resulting lessons and insights to the future development of electric vehicles, with examples from multiple countries. An important finding is that the successful diffusion of electric vehicles demands a more robust co-construction policy focus that includes tinkering with all aspects of the societal embedding process, and one involving a constellation of agents beyond policymakers and purchasers.